Workshop Pembuatan Aplikasi Keuangan Sederhana Menggunakan Appsheet di SMK N Candipuro - Heni Sulistiani; Auliya Rahman Isnain; Yuri Rahmanto; Very Hendra Saputra; Priskilia Lovika; Rido Febriansyah; Ady Chandra (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
Hard skills are one of the important things for Vocational High School Students (SMK), this is because high school students are prepared to be ready to work, especially in the era of the industrial revolution 4.0. One of the hard skills is being able to use certain applications or software. Hard skills can be obtained apart from the learning process in class, they can also be obtained through training that can improve hard skills. This Community Service activity was carried out at SMK N Candipuro Lampung Selatan, with the aim of providing training to students related to using the appsheet to make simple financial applications, with the aim that students can find out how to make simple financial applications using an appsheet so that it can be used as one of the hard skills in the field technology